Analisis Strategi Pemasaran Jasa Pembiayaan Pada PT Federal International Finance (FIF) Cabang Tenggarong - Sari, Nilam Anggar; Susanti, Susy (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract :               The purpose of this study was to formulate the right marketing strategy for FIF Tenggarong Branch in the face of business competition using SWOT analysis. Respondents in this study amounted to 33 people consisting of 28 customers and 5 employees.The results of this study indicate that (1) Based on the calculation of (Strenght) - (Weaknesses), the internal value of the factor is 0.476 which means that the FIF Tenggarong Branch has greater strength than weakness, (2) Based on Opportunities - (Threats) obtained external factors of 1,569 which means that FIF Tenggarong Branch has a greater chance of threats, (3) Based on the SWOT matrix obtained the position / strategy of FIF Tenggarong Branch is currently in an aggressive strategy position (Growth oriented strategy) located in quadrant I where this position is a very favorable position for the Tenggarong Branch of FIF in managing the strengths and opportunities owned, in terms of internal and external.The strategy that must be implemented is to support an aggressive growth policy (Growth Oriented Strategy). Keywords: marketing strategy, SWOT analysis